Anti-cyclic citrullinated peptide antibody is highly associated with rheumatoid factor and radiological defects in rheumatoid arthritis patients. Issue 12 (March 2019) - Sulaiman, Farah Nadiah; Wong, Kah Keng; Ahmad, Wan Aireene Wan; Ghazali, Wan Syamimee Wan
Abstract : Abstract: Rheumatoid arthritis (RA) is a chronic debilitating inflammatory disease affecting mainly the joint, surrounding tissue and other extra-articular structures in the body. RA can lead to destruction of bone and cartilage which may cause severe disability and it is characterized by the presence of serum rheumatoid factor (RF). The anti-cyclic citrullinate peptide (anti-CCP) antibody is another serum biomarker used in RA diagnosis with higher sensitivity and specificity. In this cross-sectional study with retrospective record review, 159 established RA patients from Hospital Universiti Sains Malaysia (HUSM) were recruited. Enzyme-linked immunosorbent assays (ELISAs) for serum RF and anti-CCP were performed. Our goal was to evaluate the significance of anti-CCP antibody in predicting the disease activity and progression in terms of radiological and extra-articular manifestations upon diagnosis. Of the 159 RA patients included in this study, mean age was 48.3 years old and majority (n = 134; 84.3%) were female. A total of 83 (52.2%) and 99 (62.3%) patients had anti-CCP antibody and RF, respectively. Mean Disease Activity Score-28 for Rheumatoid Arthritis with erythrocyte sedimentation rate (ESR) (DAS28-ESR) score for all patients was 4.74 (medium and high disease activity). Fifty-eight (36.5%) patients had radiological defects and 49 (30.8%) patients had extra-articular involvement manifested by rheumatoid nodule, pulmonary involvement, and anemia. In terms of anti-CCP antibody association with clinical and laboratory parameters, a significant co-occurrence of RF and anti-CCP antibody ( P = .002) was observed. Anti-CCP antibody was significantly associated with radiological defects in which majority of patients with such defects (n = 40/58; 68.9%) were positive for anti-CCP antibody ( P = .001). However, there was no significant difference between mean and classes of disease activity score and extra-articular manifestations between different anti-CCP antibody groups. In addition, extra-articular manifestations were not associated with high disease activity upon RA diagnosis There was a significant association between anti-CCP antibody positivity and positive RF. Radiological defects were the sole clinical parameter significantly associated with anti-CCP antibody positivity, indicating that patients positive for anti-CCP antibody should be routinely monitored for radiological defects and their onset.